A methodology to specify the weighting matrices of a direct digital control with quadratic performance index - Rara, Marcelo S.; Vilas Wuwongse; Huynh, Ngoc Phien; Radok, J.R.M; National Government of Australia (Bangkok : Asian Institute of Technology, 1984)
This research proposes and develops a procedure to specify the weighting matrices of the quadratic performance index in the control system design by the state-space approach, yielding a system which is both optimal and satisfying time response specifications. The procedure specifies the elements of the weighting matrices by relating them to the transient as well as steady-state time response specifications of the control system. An example illustrating the procedure is given.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1984